THE ADOLESCENT LEVEL OF KNOWLEDGE OF SELF-MEDICATION IN SIMPANG SELAYANG NEIGHBORHOODS, MEDAN - Romauli Anna Teresia Marbun; Klara Jeina Br Tarigan; Yanna Rotua Sihombing (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2023)
Self-medication is the most common action taken before finally deciding to see a doctor. Self-medication is known as self medication or self-medication is defined as a treatment effort using drugs purchased at pharmacies or drug stores freely without a prescription from a doctor. Self-medication is done because it is sufficient to treat health problems experienced, for example, illnesses with mild symptoms and can heal themselves in a short time such as pain, fever, cough, cold, and minor injuries. Drugs without a doctor's prescription such as free and limited free drugs are relatively safe to use for self-medication.This type of research is quantitative analytical research with descriptive. This study is to determine the level of knowledge of self-medication in adolescents in Simpang Selayang Village by approaching, observing or collecting data at once and providing education. Based on questionnaire data, it is known that the gender of female adolescents has a higher level of knowledge of self-medication than male adolescents. It can be concluded that the age level of late adolescents has a higher level of knowledge of self-medication than early adolescents. In this study, the level of knowledge of the last education of higher education towards self-medication is higher than those who have the last education either elementary, junior high or high school. The study concluded that the level of knowledge of students towards self-medication was higher than other occupations. The level of knowledge of self-medication practices in adolescents in Simpang Selayang is classified as good (62.0%).